Genomic Study of Babesia bovis Infection Level and Its Association With Tick Count in Hereford and Braford Cattle - Cavani, Ligia; Braz, Camila Urbano; Giglioti, Rodrigo; Okino, Cintia Hiromi; Gulias-Gomes, Claudia Cristina; Caetano, Alexandre Rodrigues; Oliveira, Márcia Cristina de Sena; Cardoso, Fernando Flores; Oliveira, Henrique Nunes de (Frontiers in Immunology, 2020)
Bovine babesiosis is a tick-borne disease caused by intraerythrocytic protozoa and leads to substantial economic losses for the livestock industry throughout the world. The Babesia bovis is considered the most pathogenic species, which causes bovine babesiosis in Brazil. In this regard, genomic data could be used to evaluate the viability of improving resistance against B. bovis infection level through genomic selection, as well as to a better understanding of the genetic basis of the host response to B. bovis infection using genome-wide association studies (GWAS). The objective of this study was to estimate genetic correlation between B. bovis infection level (IB) and tick count (TC); evaluate predictive ability and applicability of genomic selection, and perform GWAS using single-step GBLUP model in Hereford and Braford cattle. The IB quantification from the blood of 1,858 animals was conducted using the qPCR assays. One to three subsequent tick counts were performed by manually counting adult female ticks on one side of each animal’s body naturally exposed to ticks. Animals were genotyped using Illumina BovineSNP50 panel. The posterior mean of IB heritability estimated by Bayesian animal model in a bivariate analysis was low (0.10), and the estimations of genetic correlation between IB and TC were low as well (0.15). The cross-validation genomic prediction accuracy for IB ranged from 0.18 to 0.35, and from 0.29 to 0.32 using k-means and random clustering, respectively, suggesting that genomic predictions could be used as a tool to improve genetics for IB, especially if a larger training populations is developed. The top 10 SNPs from the GWAS explained 5.04% of total genetic variance for IB, which are located on the chromosomes 1, 2, 5, 6, 12, 17, 18, 16, 24, and 26. Some candidate genes participate in immunity system pathways indicating that those genes are involved in resistance to B bovis in cattle. Although the genetic correlation between B. bovis infection level and tick count was weak, candidate genes identified in this study seem to be involved in resistance biological processes for both traits. This study contributes to improving genetic knowledge regarding the infection of B. bovis in cattle.